Some Remarks on Bimodality Effects of the Hydraulic Properties on Shear Strength of Unsaturated Soils. Issue 9 (1st September 2015) - Ciervo, Fabio; Casini, Francesca; Papa, Maria Nicolina; Rigon, Riccardo
Abstract : Hydraulic properties affect the shear strength of unsaturated soils in terms of suction, predicted as a function of water volume in the pores. In complex pore geometries, such as soils with bimodal pore‐size distributions, suction effects on shear behavior are poorly understood. We present an analytical approach to define how a bimodal suction stress originates in such soils, which are conceptually divided into micro and macrostructures due to aggregation of a wide range of particle sizes. The results were compared with data from the literature for other soils with aggregated macrostructure or with a prevailing coarse fraction. A physically based dependence of soil shear behavior on the bimodal hydraulic behavior was observable, with the extension of the suction stress theory to a bimodal soil hydraulic response in agreement with the suction and moisture change. Depending on the soil type and the range of suctions investigated, the micro and macrostructures should prevail affecting the mechanical soil response subject to environmental loading, such as rainfall events. From a practical point of view, taking into account the bimodal structure network should be fundamental in the set‐up of proper prediction models for shallow landslides induced by rainfall.